REPOSISI DAN EKSISTENSI MADRASAH SALAFIYAH DI ERA GLOBAL - Salahuddin, Marwan (Cendekia: Jurnal Kependidikan dan Kemasyarakatan, 2013)
Abstract: Madrasah is an educational institutions have developed varied , with the times . Most madrasah became public educational institutions distinctively Muslim ,most complete knowledge of religion taught in public schools because of the number of hours of very few studies , some still remain committed madrasah as an institution that studies the Islamic sciences . Then this madrasah is referred to the Madrasah Salafiyyah . Generally, these types of madrasah teach Islamic sciences which writes by Ulama Salaf, so if it is associated with the development of science and technology in this globalization era has missed most of the material , but in fact this kind of madrasah still exist with a variety of activities . This can happen because the madrasah managers capable of adapting to changes in the global era . Old tradition that is still well maintained in order to fortify the negative influence of the various cultures that can undermine Islamic values . Similarly, the maintenance of the values as the basis for the formation of character with more emphasis on the primacy of worship and devotion to duty as a parent and teacher glorify ukhrawi approach continue to be preserved . Thus madrasah salafiyah will be more in demand , due to appear in the form of a new face, but the values still follow the previous scholars. Ø¶Ø¹Ø¨ ØØ¨ØµØ£Ù ØŒÙ†Ø§Ù…Ø²Ù„Ø§ Ù…Ø¯Ù‚Øª Ø¨ÙƒØ§ÙˆØª Ø§Ø¹ÙˆÙ†ØªÙ… ”“ Ø©ÙŠÙ…Ù„Ø³Ø¥ Ø©ÙŠÙˆØ¨Ø±Øª Ø©Ø³Ø³Ø¤Ù…Ùƒ ”“ Ø©ÙŠÙ†ÙŠØ¯Ù„Ø§ Ø©Ø³Ø±Ø¯Ù„Ø§ ØªÙ† :ØµØ®Ù„Ù… Ø©ÙŠØ¨ÙŠØ±Ø¬ØªÙ„Ø§ Ù…ÙˆÙ„Ø¹Ù„Ø§Ø¨ Ø©ÙŠÙ†ÙŠØ¯Ù„Ø§ Ø¯Ø§ÙˆÙ„Ø§ ØªÙ„Ù…ÙƒØ£ Ø±Ø®Ù„Ø§ Ø¶Ø¹Ø¨Ù„Ø§Ùˆ ØŒØ©ÙŠÙ…Ù„Ø³Ø¥ Ø©Ø²ÙŠØ¨ Ø©Ø²ÙŠÙ…ØªÙ„Ø§ Ø©Ù…Ø§Ø¹ Ø©ÙŠÙˆØ¨Ø±Øª Ø©Ø³Ø³Ø¤Ù… Ø³Ø±Ø§Ø¯Ù„Ø§ Ù†Ù… Ø«Ù„Ø§Ø«Ù„Ø§ Ø¹ÙˆÙ†Ù„Ø§Ùˆ .Ø·Ù‚Ù Ø©ÙŠÙ…Ù„Ø³Ù„Ø§ Ù…ÙˆÙ„Ø¹Ù„Ø§ Ø³Ø±Ø¯Øª Ù„Ø§Ø²Øª Ù„ ØªÙ„Ø§ Ø©Ø³Ø±Ø¯Ù„Ø§ Ø±Ø®Ù„Ø§ Ø¶Ø¹Ø¨Ù„Ø§Ùˆ ØŒØ©Ù„ÙŠÙ„Ù‚ Ø§Ù‡ØªØµØ Ø¯Ø¯Ø¹ Ù†Ù„ Ø¡Ø§Ù…Ù„Ø¹Ù„Ø§ ÙÙŠÙ„Ø£Øª Ø©ÙŠÙ…Ù„Ø³Ù„Ø§ Ø¨ØªÙƒÙ„Ø§ Ø³Ø±Ø¯Øª ”“ Ø©Ù…Ø§Ø¹ ”“ Ø©Ø³Ø±Ø¯Ù„Ø§ Ù‡Ø°Ù‡ Ù„Ø«Ù… Ù†Ø¥ . Ø©ÙŠÙÙ„Ø³Ù„Ø§ Ø©Ø³Ø±Ø¯Ù„Ø§Ø¨ ÙŠÙ…Ø³Ù„Ø§ ÙˆÙ‡ Ø©Ø³Ø±Ø¯Ù„Ø§ Ø©Ù…Ø¦Ø§Ù‚ Ø³Ø±Ø§Ø¯Ù„Ø§ Ù‡Ø°Ù‡ Ù†ÙƒÙ„ ØŒØ©Ø±Ø®Ø£ØªÙ… Ø§Ù‡Ø¯Ø§ÙˆÙ… Ø¶Ø¹Ø¨ Ù†Ø§Ùƒ ØŒØ§ÙŠØ¬ÙˆÙ„ÙˆÙ†ÙƒØªÙ„Ø§Ùˆ Ù…ÙˆÙ„Ø¹Ù„Ø§ Ù…Ø¯Ù‚ØªØ¨ Ù†Ø±ÙˆÙ‚ ÙˆÙ„ Ù‰ØªØ ØŒÙŠÙÙ„Ø§Ø³Ù„Ø§ Ù‰Ù„Ø¹ Ø©Ø³Ø±Ø¯Ù„Ø§ ØªØ¸ÙØ§ØÙˆ ØŒØ©Ù„ÙˆØ¹Ù„Ø§ Ø±ØµØ¹ Ù ØªØ§ÙŠØºØªÙ„Ø§ Ø¹Ø§ÙˆÙ†Ø£Ø¨ Ø©Ø³Ø±Ø¯Ù„Ø§ Ø¬Ù…Ø¯ Ù‰Ù„Ø¹ Ø±Ø¯Ø§Ù‚ Ø©Ø³Ø±Ø¯Ù„Ø§ Ù‡Ø°Ù‡ Ù…Ø¸Ù†Ù… Ù†Ù„ ØŒØ©ØªØ¨Ø§Ø« ÙƒÙˆÙ„Ø³Ù„Ø§ Ù†ÙŠÙˆÙƒØªÙ„ Ù…ÙŠÙ‚Ù„Ø§ Ù‰Ù„Ø¹ ÙƒÙ„Ø°Ùƒ Ø¸ÙØ§ØªÙˆ .Ø©Ù…Ø§Ù‘ Ø¯Ù„Ø§ ØªØ§Ø±Ù‘ Ø«Ø¤Ù„Ø§ Ù†Ø¹ Ø©ÙŠÙ…Ù„Ø³Ù„Ø§ Ù…ÙŠÙ‚Ù„Ø§ Ø¸Ø§ÙÙ„ Ø©Ù„Ø§ØµÙ„Ø§ Ø©ÙŠØ¯Ù‚Ù„Ø§ Ù…ÙŠÙ‚Ù„Ø§ Ù†ÙˆÙƒØªØ³ ØŒØ§Ù‡Ù„Ùƒ Ù‡Ø°Ù‡Ø¨ .ÙŠÙˆØ±Ø®Ù„Ø§ Ù„Ø®Ø¯Ù„Ø§Ø¨ ÙŠÙ…Ù„Ø¹Ù„Ø§Ùˆ Ù†ÙŠØ¯Ù„Ø§ÙˆÙ„Ø§ Ù…Ø§Ø±ÙƒØ¥ Ø¨ÙˆØ¬ÙˆÙˆ Ø©ÙŠØ¯ÙˆØ¨Ø¹Ù„Ø§Ùƒ Ø©Ø¯Ø§Ø¨Ø¹Ù„Ø§ ØÙˆØ± Ù„Ø¥ Ù‡Ø§ØªÙ„Ø§Ø¨ .Ù„Ø§ØµÙ„Ø§ ÙÙ„Ø³Ù„Ù„ Ù…ÙŠÙ‚Ù„Ø§ ØªØ¹Ø¨ØªØ§ Ø§Ù‡Ù†ÙƒÙ„ Ø¯ÙŠØ¯Ø¬ Ù‡Ø¬ÙˆØ¨ ØªØ±Ù‡Ø¸ Ø§Ù‡Ù†Ù„ ØŒØ¨Ù„Ø·Ù„Ø§ ØªØ§Ø¨ØºØ± Ø¹Ø¶ÙˆÙ… Ø©ÙŠÙÙ„Ø³Ù„Ø§ Ø³Ø±Ø§Ø¯Ù„Ø§ Ù‡Ø°Ù‡